This article reads the options for further quality improving of training for aviation personnel in higher education insti-tutions of the Russian Federation via introduction of innovative forms and methods of modernization of educational pro-cess in accordance with international educational standards of new generation. - Yu. M. Сhinyuchin; B. P. Eliseev; A. S. Borzova; V. P. Berlev (Научный вестник МГТУ ГА)
This article reads the options for further quality improving of training for aviation personnel in higher education insti-tutions of the Russian Federation via introduction of innovative forms and methods of modernization of educational pro-cess in accordance with international educational standards of new generation.